Morphological Changes In Cdse Layers Deposited On Porous P+-Gaas;Correlation With Optical And Structural Proprieties - A.Smida; N.Haj Mohamed; H. Ezzaouia (Algerian Journal of Research and Technology (AJRT), 2020)
Synthesized-CdSe nanoparticles were deposited by using spin coating method onto porous GaAs substrate elaborated by an electrochemical process. The surface morphology of deposited CdSe layer was investigated by scanning electron microscopy (SEM), the surfaces’ roughness and morphology after the Growth the CdSe nanoparticles modification was exhibited by atomic force microscopy (AFM), X- ray diffraction (XRD techniques proved the incorporated of CdSe nanoparticles on the surface states. SEM imaging shows that the CdSe was penetrated deeply in the porous structure down to the bottom and reaching the interface GaAs/porous GaAs. It was also observed that the reflectivity decreased after the deposition process of CdSe nanoparticles due to the size of CdSe nanoparticles. In addition, the photoluminescence (PL) spectroscopy exhibits a new intense peak at 2.08 eV due to CdSe nanoparticles deposition. It was attributed to CdSe nanoparticles with narrow particle-size distribution uniformly coated on the surface.